Sunna Gua Findings of the soul: Spiritual and identity understandings of indigenous ancestral psychology (2020)
After years of ancestral journeys of the human psyche and the development of four transcendental research macroprojects in the field, it is time to undertake the method of ancestral walking on the living system of mother earth and her human son as a verifiable sense of essential nature and substantial of the soul. Method of walking in the loving order of the ancestors, the father and the mother, the cosmos and the earth, the sun and the moon.Co-responsible planting of bridging the integration of the ancestral left hand and the western right hand from the sensible, the construction of mythical thought as great logos, Huitaqa (thought) of the path of the soul (Sunna Gua), of the theory on the radical cosmogonic bases and epistemological of the spiritual foundation and of the individually and collectively mythical, mystical, botanical and ritualistic therapeutics of the human psyche.Saved the modernist shames, a writing is presented on the proper as philosophy, science and psychology, for this reason, the scope of the present emergence of the quantum in the sacred fabric of a founding myth that recognizes and honors in psychism the evolutionary force of human conscience, an ancestral bet of increases of conscience in the confidence for the power of this soul that is sown fertile for the healing, transformation and evolution towards to the great spirit. What can a reader find in your narrative? Perhaps a sense of the lost and absent not clarified, the great illness of the contemporary psyche, the lack of faith, the absolute loss of confidence in the mythical and sacred presuppositions of the traditions that build culture, for the same reason the urgency of recovery from a stark bridging of law of origin to an ancestral psychology that consolidates such a human pretense of life in the life of the planet.